Planting pattern and agronomic traits of corn cultivars in two fertility levels - Sangoi, Luís (2014)
This field experiment was conducted in Lages, SC, Brazil, during the 1986/87 and 1987/88 growing seasons, in, order to evaluate the effects of planting pattern and agronomic traits of a hybrid and a variety of corn in two fertility levels. At level one, no fertilizer was applied, and at level two 20kg of N, 80kg of P205 and 70kg of K20 were applied, during planting operation plus 80 kg of Nafter plant emergence. The genotypes tested were Agroceres 28 C and Empase 152-Oeste, sowed in the following planting patterns: one, two, three and four plants per hill. Fertilized plots showed higher grain yield tan those not, fertilized, due to more grains per ear and ears per plant presented in the fertilized trait. The hybrid Ag 28 C produced higher grain yield than the variety Oeste. No significant effects of planting pattern on grain yield and plant lodging of the cultivars were observed.